Effects of livestock grazing on Anemone coronaria L. in drylands: Implications for nature conservation. Issue 1 (26th April 2018) - Stavi, Ilan; Shuker, Shimshon; Barkai, Daniel; Knoll, Yaakov M.; Zaady, Eli
Abstract : Grazing in nature reserves, or other sensitive lands, could affect the abundance of important plant species. In the Mediterranean basin, the Anemone coronaria is considered a flagship geophyte species. Studies conducted in the Mediterranean region of northern Israel showed that livestock grazing increased the abundance of A. coronaria . This was attributed to the consumption of other herbaceous vegetation species, resulting in better accessibility of A. coronaria to sunlight. Also, it was suggested that consumption of this species is limited due to its toxicity. The objective of this study was to investigate the impact of livestock on the abundance of A. coronaria, and on specific soil properties in a dryland environment, where primary productivity is determined by water availability. A long‐term study was established in the Israeli Negev, where early‐, mid‐, and late‐season grazing treatments took place over the course of a decade, and studied over three consecutive years between 2013/2014 and 2015/2016. The study revealed that the abundance of A. coronaria followed the order of non‐grazing (control) > late‐season grazing > mid‐season grazing > early‐season grazing. However, this effect was not significant ( p = .0668). One way or another, the largest adverse impact of early‐season grazing is attributed to consuming fresh and not yet toxic shoots of A. coronaria at that phenological stage. The soil properties were studied in summer 2016. The analysis showed a significant increase in bulk density under all of the grazing treatments compared with those in the control plots. It was concluded that, in drylands, trampling over wet soil during the growing season increases its compactability, degrading the soil‐moisture status, and limiting A. coronaria abundance. Recommendations for nature conservation in drylands are, therefore, to negate grazing during A. coronaria 's early‐growing season, as well as shortly after rain events when the soil moisture level is high. Abstract : The largest adverse impact of the early‐season grazing is attributed to the consuming of fresh and not yet toxic shoots of A. coronaria at that phenological stage. Also, trampling over wet soil during the growing season increases its compactability, degrading the soil‐moisture status, and limiting the A. coronaria frequency. Recommendations for nature conservation in drylands are, therefore, to negate grazing during A. coronaria 's early‐growing season, as well as shortly after rain events when the soil moisture level is high. e00053